Spatially Compounding Drought Events in Brazil - Gabriela C. Gesualdo; Marcos R. Benso; Eduardo M. Mendiondo; Manuela I. Brunner (Water Resources Research)
Abstract Spatially compounding drought events affect multiple locations simultaneously, severely affecting food, water, energy, human health, and infrastructure sectors. Despite the cascading impacts and challenges compound droughts impose on society, we still lack an in‐depth understanding of spatially connected drought occurrences. Given the complexity and costs of droughts in Brazil, identifying regions prone to co‐experiencing droughts is critical for developing effective adaptation measures. Here, we develop a novel framework to assess the spatial co‐occurrence of hydrological drought events, which can be adapted for global applications to evaluate spatially compounding drought. This framework involves extracting drought data from individual catchments and calculating the co‐occurrence of droughts across all catchments. We apply this method to investigate the spatial connectedness of droughts in 511 Brazilian catchments over 39 years (1983–2022). Additionally, we classify catchments based on drought duration, intensity, deficit, number of events, and spatial connectedness to identify regions with similar drought behavior. Our findings reveal significant variability in drought characteristics and connectedness across Brazil, with the Central‐Northeast and Northwest Amazon regions being most affected by multiple and widespread droughts. We identify five distinct regions in Brazil that exhibit common drought behaviors, sharing attributes such as aridity, catchment area, and precipitation seasonality. These regions hold the potential to guide future adaptation plans for managing hydrological compound extremes at both the catchment and regional scales, including the development of risk pool networks. Our results underscore the importance of considering the interactions of spatially compounding hydrological droughts in risk assessments and adaptation strategies.